2019
DOI: 10.9734/isrr/2019/v8i230097
|View full text |Cite
|
Sign up to set email alerts
|

Azole Resistance and Detection of the ERG11 Gene in Clinical Candida albicans Isolated from Pregnant Women with Vulvovaginitis Attending Federal Medical Centre, Yenagoa, Nigeria

Abstract: Introduction: Candida albicans is one of the most important aetiological agents causing vaginal candidiasis in pregnant women. Most women will experience at least one episode during their reproductive years. Antifungal resistance is a particular problem with Candida infections. Some types of Candida are increasingly resistant to the first-line and second-line antifungal medications. Objective: To investigate the azole susceptibility of Candida albicans (C. albicans) from pregnant vulvovaginal candidiasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
(65 reference statements)
1
3
0
Order By: Relevance
“…In [29]. In China, studies on ERG11 gene mutations in C. albicans isolated in vulvovaginitis (p < 0.05) showed a prevalence of the detected gene of 8.4% [17] and 12.2% [30]; which is similar to ours.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In [29]. In China, studies on ERG11 gene mutations in C. albicans isolated in vulvovaginitis (p < 0.05) showed a prevalence of the detected gene of 8.4% [17] and 12.2% [30]; which is similar to ours.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, the ERG11 gene was detected in C. albicans isolates resistant to azoles. In Nigeria, similar studies were carried out showing the presence of the ERG11 gene at 11.18% in strains of Candida resistant to Fluconazole isolated from vulvovaginitis (p > 0.05) and 88.89% in C. albicans strains all resistant to the azoles Fluconazole and Voriconazole isolated only in pregnant women [ 29 ]. In China, studies on ERG11 gene mutations in C. albicans isolated in vulvovaginitis (p < 0.05) showed a prevalence of the detected gene of 8.4% [ 17 ] and 12.2% [ 30 ]; which is similar to ours.…”
Section: Discussionmentioning
confidence: 96%
“…in the female genital tract, which has been known as a challenge for gynecologists and infected patients for decades. Although C. albicans is known as the most common cause of VVC infection, other Candida species with high drug resistance, such as C. glabrata, have recently been replaced [7,12,29,30] . Studies have suggested that the diagnosis of vulvovaginitis caused by other Candida species may be very effective in selecting a successful treatment protocol [26,31] .…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, due to frequent treatment failures and recurrences, this infection has challenged the life quality of infected women as well as physicians [9] . Although C. albicans is known as the most common cause of VVC, there is a significant trend towards the emergence of other species such as C. glabrata, C. parapsilosis, and C. krusei, which show more resistance to the first-line antifungal treatments [10][11][12] . Hence, laboratory diagnosis seems necessary to identify Candida species involved in VVC.…”
Section: Introductionmentioning
confidence: 99%